Wooden furniture purchase attributes: a Malaysian consumers' perspective - Mohamed , Shukri; Tan, Poh Yi (Universiti Putra Malaysia Press, 2008)
Consumers evaluate a product based on various attributes when making a purchase decision. In this paper, the types of attributes important of Malaysian consumers when purchasing wooden living room furniture were investigated. Data were gathered from questionnaire survey of 115 mall-intercepted adult respondents on the perceived importance of five products and two store-related attributes. It was found that (in rank order) quality, design, and price of the wooden furniture were important product-related purchase attributes for Malaysian consumers. These consumers are expected to limit their purchase to neighbourhood outlets as the location of retail outlets is perceived as an important store-related attribute. Demographic characteristics of the respondents have an influence on the perceived importance of the attributes.